Log in

Connect faster with

Register

Signup faster with


|   Education without borders.
Menu
a Guest

10th

Posted in Math, asked by anisha, 6 years ago. 1710 hits.

0

(1/a)+(1/b)+(1/x)=1/a+b+x

we will expand the L.H.S and do cross multiplication herr

=> (bx+ax+ab)/abx=1/a+b+x

=>( bx+ax+ab)(a+b+x)=abx

=> (bx+ax+ab)a+(bx+ax+ab)b+(bx+ax+ab)x=abx

=>abx+a^2x+a^2b+b^2x+abx+ab^2+bx^2+abx+ax^2=abx

we will take the R.H.S into L.H.S then

abx+a^2x+a^2b+b^2x+abx+ab^2+bx^2+abx+ax^2-abx=0

now we will rewrite the equation

 = x^2(a+b)+x(a^2+ab+ab+ab+b^2-ab)+a^2b+ab^2=0

= x^2(a+b)+x(a^2+2ab+b^2)+ab(a+b)=0

=x^2(a+b)+x(a+b)^2+ab(a+b)=0

in all the above terms,(a+b) we have common,so

(a+b)(x^2+(a+b)x+ab)=0

now, it will come ,x^2+(a+b)x+ab=0

     now again we rewrite it, x^2+ax+bx+ab=0

                                       x(x+a)+b(x+a)=0

                                        (x+a)(x+b)=0

                                        x+a=0,x+b=0

                                          x=-a,x=-b

we can solve this type problems in many ways.i think its useful and simple way to understand the students

Venkat Nagendra Thati
Venkat Nagendra Thati - 6 years ago
Ask Venkat Nagendra Thati for further help.
Report
Please register/login to answer this question. 
- Just now

0

a Guest
Just now
× Attachments/references, if any, will be shown after refreshing the page.
/homework-help
/homework-help/get_answer/284
/homework-help/save_reply/284
/homework-help/save_answer/284
/homework-help/accept_answer/284
/homework-help/unaccept_answer/284
/homework-help/unpublish_answer/284
/homework-help/delete_answer/284
/homework-help/update_answer/284
/homework-help/like/284
/homework-help/dislike/284
/homework-help/report_answer/284
/homework-help/report_question/284
/homework-help/save_bounty/284